Colonization by macroinvertebrates on an artificial substrate and comparison with a natural substrate in a floodplain: A short time study in the rainy season - da Silva, Carolina Vieira [UNESP]; Henry, Raoul [UNESP] (Oecologia Australis, 2017)
Understanding how the process of colonization by taxa in different types of habitat takes place is necessary to preserve their diversity. The aim of this study was to analyze the process of colonization by macroinvertebrates on an artificial substrate with morphology similar to that of the roots of aquatic macrophytes Ricciocarpus natans and Spirodela intermedia, which were present in the environment investigated. The hypothesis is that the values of total density on the artificial substrate will show a tendency similar to that of a macrophyte stand, but with a different taxonomic composition. The differences in taxa density and composition associated with the artificial substrate and macrophytes were significant. The total density and richness on the artificial substrate did not follow an upward curve with a significant increase in the number of individuals during the experiment, probably due to the heavy rainfall observed. The variation in the density values in both substrates shows that the macroinvertebrate community was maintained through an “emigration” and “immigration” dynamic. Our hypothesis was confirmed only in relation to the taxonomic composition. The colonization of the artificial substrate by macroinvertebrates might have been more efficient had the environment not received frequent rains, which affected the physical stability of the macroinvertebrate community. Therefore, intrinsic sampling site characteristics may have attenuated the effect of the flood pulse on the macroinvertebrate communities, since only oscillations in the density values of the taxa were observed, rather than their exclusion.
Keywords: Ecological succession; Hydrological disturbance; Phytofauna; Ricciocarpus natans; Spirodela intermedia